Harnessing the Potential of Bacillus altitudinis MT422188 for Copper Bioremediation - Khan, Maryam; Kamran, Muhammad; Kadi, Roqayah H.; Hassan, Mohamed M.; Elhakem, Abeer; Sakit ALHaithloul, Haifa Abdulaziz; Soliman, Mona H.; Mumtaz, Muhammad Zahid; Ashraf, Muhammad; Shamim, Saba (Frontiers in Microbiology, 2022)
The contamination of heavy metals is a cause of environmental concern across the globe, as their increasing levels can pose a significant risk to fragile ecosystems and public health. This study aimed to evaluate the ability of a copper (Cu) resistant bacterium, characterized as Bacillus altitudinis MT422188, to remove Cu from contaminated industrial wastewater. Optimum growth was observed at 37 °C, pH 7, and 1 mM phosphate, respectively. Effective concentration 50 (EC50), minimum inhibitory concentration (MIC), and cross-heavy metal resistance pattern was observed at 5.56 mM, 20 mM, and Ni>Zn>Cr>Pb>Ag >Hg, respectively. Biosorption of Cu by live and dead bacterial cells in its presence and inhibitors 1 and 2 (DNP and DCCD) was suggestive of an ATP-independent efflux system. B. altitudinis MT422188 was also able to remove 73 mg/L and 82 mg/L of Cu at 4th and 8th day intervals from wastewater, respectively. The presence of Cu resulted in increased GR (0.004 ± 0.002 Ug-1FW), SOD (0.160 ± 0.005 Ug-1FW), and POX (0.061 ± 0.004 Ug-1FW) activity. Positive motility (swimming, swarming, twitching) and chemotactic behavior demonstrated Cu as a chemoattractant for the cells. Metallothionein (MT) expression in the presence of Cu was also observed by SDS-PAGE. Adsorption isotherm and pseudo kinetic order studies suggested Cu biosorption to follow Freundlich isotherm as well as second order kinetic model, respectively. Thermodynamic parameters such as Gibbs free energy (∆G°), change in enthalpy (∆H°=10.431 kJ/mol), and entropy (∆S°=0.0006 kJ/mol/K) depicted the biosorption process to a feasible, endothermic reaction. FTIR, SEM, and EDX analyses revealed the physiochemical and morphological changes in the bacterial cell after biosorption, indicating interaction of Cu ions with its functional groups. Therefore, these features suggest the potentially effective role of B. altitudinis MT422188 in Cu bioremediation.